Phase I Studies of Acebilustat: Pharmacokinetics, Pharmacodynamics, Food Effect, and CYP3A Induction. Issue 1 (28th October 2016) - Elborn, JS; Bhatt, L; Grosswald, R; Ahuja, S; Springman, EB
Abstract : Acebilustat is a new once‐daily oral antiinflammatory drug in development for treatment of cystic fibrosis (CF) and other diseases. It is an inhibitor of leukotriene A4 hydrolase; therefore, production of leukotriene B4 (LTB4) in biological fluids provides a direct measure of the pharmacodynamic (PD) response to acebilustat treatment. Here we compare the pharmacokinetics (PK) and PD between CF patients and healthy volunteers, and investigate the food effect and CYP3A4 induction in healthy volunteers. No significant differences between study populations were observed for peak plasma level (Cmax ) or exposure (AUC). In healthy volunteers, a shift in time to Cmax (Tmax ) was observed after a high‐fat meal, but there was no change in AUC. LTB4 production was reduced in the blood of both populations and in sputum from CF patients. Acebilustat did not induce CYP3A4. These results support continued clinical study of once‐daily oral acebilustat in CF at doses of 50 and 100 mg.